Urea Formaldehyde Composites Reinforced with Sago Fibres Analysis by FTIR, TGA, and DSC - Chiang, Tay Chen; Sinin, Hamdan; Mohd Shahril, B.Osman (Hindawi Publishing Corporation, 2016)
Agriculturalmaterial or biomaterial plays an important role in the field of fibre-reinforced polymericmaterials with their new range of applications and achieves the ecological objective. Composition and structure of the nature fibre and matrix must be taken into consideration for the end use. In this project, Sago fibre particleboard bonds with Urea Formaldehyde to form composite. Fourier Transform Infrared (FTIR) spectra are used to characterize the Sago/Urea Formaldehyde composite in terms of their functional group and bonding. Sago/UF composite with smaller particle and higher loading of fibre with 15wt% of UF matrix has the higher curing properties. The composite will have a denser structure by adopting bigger particle and higher loading of UF matrix. The Sago/UF composite only endures a single stage of decomposition.Thermal stability results indicate that particle size, particle/matrix interface adhesion, and particle loading have great influence on the thermal properties of the composites.